From Waves to Diagnoses: Decoding Electrocardiogram for Improved Cardiac Care - Sharanya Varaganti; Rajaputana Lakshmi Manisha; Sudhakar Muvvala (Archives of Medicine and Health Sciences)
The electrocardiogram (ECG) is a fundamental tool in cardiology, providing invaluable insights into cardiac physiology and detecting various abnormalities. This review article presents a comprehensive overview of ECG interpretation, focusing on the procedure, application, and methodology. The placement of electrodes, ECG paper speed, and measurements of intervals and blocks are discussed in detail. The article emphasizes the importance of a systematic approach to ECG interpretation, highlighting six main sections: determination of heart rhythm, calculation of heart rate, assessment of intervals and blocks, analysis of atrial depolarization patterns, assessment of ventricular depolarization complexes, and delving into the intricate characteristics of ST segments and exploration of the electrocardiographic T-wave manifestations. Specific criteria for identifying abnormalities in each section are provided, along with their associated etiologies and clinical implications. Furthermore, the limitations of ECG as a diagnostic tool are acknowledged, emphasizing the need for clinical correlation and consideration of additional tests. The abstract encapsulates the breadth and depth of the review, conveying the relevance and the profound significance of ECG interpretation in the realm of clinical practice and scientific inquiry.